Desain Model Tari Kreatif Berbasis Etnik Dalam Perkuliahan Seni Tari Di PGSD FKIP Universitas Jambi - Destrinelli Destrinelli; Suci Hayati (Jurnal Gentala Pendidikan Dasar, 2020)
This learning design was developed based on the principles of Jambi regional dance with four basic attitude groupings, namely the attitude of the head, body, hands, and feet. This research is a Research and Development (RnD) research by adopting the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The research data were obtained through questionnaires, observation, tests, and interviews. Qualitative research data is a description of development procedures, ethnic-based creative dance model designs for dance arts courses at PGSD. The results of the analysis are used by the researcher as a reference for designing the expected dance learning model. The design stages are designed to produce a creative dance model design prototype that is developed. the resulting prototype, validated to experts and tested on practitioners as a step of the development phase. Ethnic-based creative dance model designs are valid, and practically implemented for the effectiveness of model design. The evaluation stage is carried out at each stage (formative) to make it easier to detect development problems early so that the final (summative) evaluation focuses more on the implementation of the learning model. Through the ADDIE development phases, the ethnic-based creative dance model design model is based on the basic attitudes of Jambi regional dance, namely 8 forms of head attitudes, 18 hand attitudes, 13 body postures, and 28 attitudes. In the creative process of students, all the basic attitudes of this regional dance can be expressed in motifs, phrases, sentences, and clusters. The process of exploration in creative dance will support students' creativity in dance expression.